Cryptography Algorithms. - Massimo Bertaccini; PACKT (GB: Packt, 2024)
Get a head start in real-world cryptography by learning the logic of algorithms that defend against attacks, and explore the latest in IoT homomorphic encryption and quantum cryptography Purchase of the print or Kindle book includes a free eBook in PDF format. Key Features Explore the basic principles and history of cryptography Identify key vulnerabilities and evaluate how cryptographic algorithms defend against attacks Become a forward-thinking cryptographer by learning the new protocols in zero knowledge, homomorphic encryption and quantum cryptography Book Description This updated edition takes you on an journey through the realm of cryptographic science, providing an in-depth exploration of its history, principles, and the latest cutting-edge developments. You will learn the mathematical logic of how algorithms encrypt and decrypt messages, introducing more complex math as the book progresses. By getting your foot in the door with how elliptic curves, zero knowledge protocols, homomorphic encryption, and quantum computing shape today's cybersecurity landscape and its attacks and defenses, you will have the groundwork on which to build professional cryptographic experience. This edition will help keep you up to date with the most innovative cryptographic algorithms, ensuring you're well-prepared to navigate the rapidly evolving world of data privacy and cybersecurity. With a focus on emerging trends and challenges, including quantum cryptography you'll acquire the knowledge needed to stay at the forefront of this dynamic field. With the latest updates and an expanded scope, this new edition ensures you're well-prepared to face the ever-evolving landscape of cybersecurity with confidence and expertise. What you will learn Get to grips with essential encryption algorithms and their logical basics Identify the key vulnerabilities of AES, RSA, and many other symmetric and asymmetric algorithms Apply the logic and mathematics behind cryptographic attacks on asymmetric encryption Discover emerging technologies like zero-knowledge protocols and homomorphic encryption Understand fundamentals of lightweight encryption for IoT and discover a new algorithm in this field Dive deep into quantum cryptography with the Shor and Grover algorithms Who this book is for This book is for beginners who are IT professionals, students, cybersecurity enthusiasts, and anyone who wants to develop skills in modern cryptography and build a successful cybersecurity career. The book systematically addresses mathematical issues related to the algorithms that may arise. However, a prior knowledge of university-level mathematics, algebra, its main operators, modular mathematics, and finite fields theory is required. Some knowledge of elliptic curves and quantum computing, especially matrices and plotting curves would also be beneficial to get the most out of this book.
Data in extended ASCII character set.
Mode of access: Internet.